Splenosis mimicking metastatic abdominal and pelvic tumours in a 12-year-old female patient - Olejarz, Anna; Dryjka, Krzysztof; Stobiecka, Martyna; Stygar, Patrycja; Szczepański, Tomasz; Bulsa, Joanna; Pasierbek, Michał; Małdyk, Jadwiga; Korlacki, Wojciech; Pobudejska-Pieniążek, Aneta (Pediatria Polska - Polish Journal of Paediatrics, 2023)
Splenosis is a heterotopic autotransplantation of splenic tissue after rupture of the splenic capsule caused by injury or during elective splenectomy in the management of haematological diseases. Splenosis might cause nonspecific abdominal symptoms but is usually asymptomatic, and it is diagnosed accidentally as an abdominal tumour. It is rarely diagnosed in the paediatric population. We describe a 12-year-old female patient with hereditary spherocytosis admitted to the hospital 3 years after elective splenectomy and cholecystectomy. In medical imaging abdominal and pelvic tumours together with enlarged lymph nodes were found. During laparoscopic surgery many nodules were found with morphology similar to splenic tissue in the omentum, on the surface of small intestine, colon and peritoneum. Results of histopathological examination confirmed splenosis. Splenosis should be considered in differential diagnosis of abdominal tumours in paediatric patients with a history of elective splenectomy or spleen injury.